Confirmatory Factor Analysis of Determinants of Entrepreneurship Career Inclination among Entrepreneurship Club Members in Secondary School/ Analisis Faktor Pengesahan Bagi Peramal Kecenderungan Kerjaya Keusahawanan dalam Kalangan Ahli Kelab Keusahawanan Sekolah Menengah (Sains Humanika, 2021)
Entrepreneurship is a tool that the Malaysian Governmentsed to uplift income from the middle-income trap. Therefore, this study aims to identify the predictor factors that influence the inclination of entrepreneurship club members towards the entrepreneurship career by using factor analysis to achieve the Government goal through the Ministry of Education Malaysia.  In other words, this study uses several tests related to validation factor analysis to determine the predictor factors that influence the propensity of entrepreneurship club members towards entrepreneurship careers. This study involved 161 respondents who were members of secondary school entrepreneurship clubs in the State of Terengganu who were randomly selected.  Data gathered were analyzed using Statistical Package for the Social Sciences (SPSS) involving factor analysis and descriptive test. The factor analysis has identified nine predictor factors. The first predictor factor is role model, followed by a barrier, social identity, personality, entrepreneurship skill, social norm, financial, entrepreneurship knowledge, and prosperity. Prosperity was the new predictor factor that was identified using factor analysis in this research. The descriptive test found that the most influenced predictor factor of the entrepreneurship career inclination was finance, followed by personality, social identification, role model, social norm, prosperity, and barrier. Meanwhile, entrepreneurship knowledge was found as a predictor factor which uncertain in influencing the entrepreneurship career inclination among secondary school entrepreneurship club members in the State of Terengganu. The results of this study imply that the Government should give financial factors the priority through the Ministry of Education in formulating policies towards producing more young generation of entrepreneurs in Malaysia because that predictor has a positive impact on secondary school students who were the members of entrepreneurship clubs.
Keywords: Confirmatory factor analysis; predictor factor; entrepreneurship career inclination; entrepreneurship club member; secondary school